AN INTEGRATION OF TRADITIONAL ECOLOGICAL KNOWLEDGE AND CASE-BASED LEARNING IN STEM COURSE: ITS CORRELATION TO TEACHER STUDENTS’ ABILITY IN DESIGNING WORKSHEET - Yasmine Khairunnisa; Arif Sholahuddin; Ilma Arasti; Nanda Fidia Safitri (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
The integration of science and local knowledge is still rarely found in the learning media used in lectures. This has an impact on the lack of meaningful learning and students' ability to create student worksheets. This study applied a case-based learning strategy integrated with traditional ecological knowledge to evaluate the ability of prospective teacher students to design student worksheets, so this study aimed to determine the correlation between the two variables. The sample for this study was 73 prospective science teacher students who programmed the STEM course. The study used a one-shoot case design and the results showed that (1) students' ability to design TEK-based worksheets increased from meeting 1 to meeting 3 after the implementation of the CBL strategy, and (2) there was a positive and strong relationship between the implementation of the CBL strategy and the ability of students to design TEK-based worksheets. So, the CBL strategy is appropriate to use in STEM lectures to improve students' ability to design worksheets.